Penegakan Hukum terhadap Pelanggaran Keimigrasian: Studi di Kantor Imigrasi Kelas II Non TPI Kediri Jawa Timur - Rijal, Najamuddin Khairur (Jurnal Ilmu Hubungan Internasional LINO, 2024)
This research discusses the law enforcement by the Class II Non TPI Kediri Immigration Office against immigration violations that occur in its area, particularly residence permits. This is based on the socio-economic development in the working area of the Kediri Immigration Office, including Kediri City, Kediri Regency, Jombang Regency, and Nganjuk Regency. This socio-economic development has implications for the increasing number of foreigners who enter and live in the area, both to work for various companies, to become students or students in various schools/Islamic boarding schools and universities, as well as for other purposes. This has an impact on various immigration violations that have occurred, especially those related to residence permits. Therefore, this study seeks to answer questions how law enforcement against immigration violations at the Kediri Immigration Office. The research approach is descriptive-qualitative through data collection by observation and literature study. The results showed that the Kediri Immigration Office has carried out its duties and functions to enforce the law against immigration violations through immigration administrative action by deportation. Deportation is carried out in accordance with the procedures and provisions for foreign citizens who are proven to have violated their residence permit.